Large Cell Neuroendocrine Carcinoma Harboring an Anaplastic Lymphoma Kinase (ALK) Rearrangement with Response to Alectinib - Hayashi, Nobuyoshi (Intern Med, 2017)
Anaplastic lymphoma kinase (ALK) rearrangement is most commonly observed in lung adenocarcinoma in a subset of lung cancer. Large cell neuroendocrine carcinoma (LCNEC) harboring an ALK rearrangement is very rare. Based on the findings from a transbronchial lung biopsy, a 75-year-old non-smoking woman was diagnosed with LCNEC with multiple liver and bone metastases. After seven cycles of cytotoxic chemotherapy, her genotype testing demonstrated ALK rearrangement. Subsequently, she was administered alectinib and exhibited a partial response.